2018
DOI: 10.1101/292011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HDAC11 Suppresses the Thermogenic Program of Adipose Tissue via BRD2

Abstract: Little is known about the biological function of histone deacetylase 11 (HDAC11), which is the lone class IV HDAC. Here, we demonstrate that deletion of HDAC11 in mice stimulates brown adipose tissue (BAT) formation and beiging of white adipose tissue (WAT). Consequently, HDAC11-deficient mice exhibit dramatically enhanced thermogenic potential and, in response to high fat feeding, attenuated obesity, insulin resistance, and hepatic steatosis. Ex vivo and cellbased assays revealed that HDAC11 catalytic activit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The genes associated with the DMR were functionally categorized and evaluated for gene pathway association utilizing the KEGG database, as described in the Methods. Several metabolic related pathways were identified, and literature searches of many of the genes revealed several genes associated with adipogenesis [63,64] adipocyte beiging/browning [65,66], insulin resistance [67][68][69], and lipolysis [70,71]. Changes in these functions in the adipocyte and adipocyte precursors may promote obesity and metabolic dysregulation [72].…”
Section: Discussionmentioning
confidence: 99%
“…The genes associated with the DMR were functionally categorized and evaluated for gene pathway association utilizing the KEGG database, as described in the Methods. Several metabolic related pathways were identified, and literature searches of many of the genes revealed several genes associated with adipogenesis [63,64] adipocyte beiging/browning [65,66], insulin resistance [67][68][69], and lipolysis [70,71]. Changes in these functions in the adipocyte and adipocyte precursors may promote obesity and metabolic dysregulation [72].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HDAC11 enzymatic activity seems to be necessary to inhibit adipocyte gene expression (Bagchi et al, 2018). This also germinated the use of HDAC11 selective small‐molecule inhibitors to increase energy expenditure to achieve the purpose of antiobesity.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC11 is involved in regulating the process of regulating metabolism and obesity (Bhaskara, 2018; L. Sun et al, 2018). Researchers have studied the biological functions of HDAC11 and found that inhibiting HDAC11 could increase the body's energy consumption to treat obesity and metabolic diseases (Bagchi et al, 2018). The loss of HDAC11 promoted the ability to generate heat, increased energy consumption, and promoted uncoupling protein‐1 expression, thereby enabling the metabolic clearance store.…”
Section: Hdac11 In Obesity‐related Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Sirtuins, HDAC11 also possesses acylase activity. Determination of defatty-acylase activity is considered an alternative method of identifying HDACs, and zinc-dependent HDACs showed notable differences in activity ( 67 , 68 ). HDAC11 participates in oligodendrocyte progression and promotes oligodendrocyte differentiation ( 69 ).…”
Section: Hdac Classificationsmentioning
confidence: 99%